2018
DOI: 10.1016/j.tplants.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Carbon/Nitrogen Metabolic Balance: Lessons from Cyanobacteria

Abstract: Carbon and nitrogen are the two most abundant nutrient elements for all living organisms, and their metabolism is tightly coupled. What are the signalling mechanisms that cells use to sense and control the carbon/nitrogen (C/N) metabolic balance following environmental changes? Based on studies in cyanobacteria, it was found that 2-phosphoglycolate derived from photorespiration and 2-oxoglutarate from the Krebs cycle act respectively as the carbonand nitrogen-starvation signals, and their concentration ratio l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(94 citation statements)
references
References 87 publications
(182 reference statements)
1
91
0
2
Order By: Relevance
“…The gene expression variation between the mutant and the wild type may also be a result of the lowered sulfane sulfur in the mutant, as sulfane sulfur is a known signaling molecule participating in many physiological processes in eukaryotes (58). And from our results, we infer that carbon and sulfur metabolisms can be linked via sulfane sulfur just like carbon and nitrogen metabolisms in cyanobacteria (60,61). As we know, sulfane sulfur can perform as a reductant to help relieve oxidative stress (35,37).…”
Section: Functions Of Sqr In Cyanobacteriamentioning
confidence: 63%
“…The gene expression variation between the mutant and the wild type may also be a result of the lowered sulfane sulfur in the mutant, as sulfane sulfur is a known signaling molecule participating in many physiological processes in eukaryotes (58). And from our results, we infer that carbon and sulfur metabolisms can be linked via sulfane sulfur just like carbon and nitrogen metabolisms in cyanobacteria (60,61). As we know, sulfane sulfur can perform as a reductant to help relieve oxidative stress (35,37).…”
Section: Functions Of Sqr In Cyanobacteriamentioning
confidence: 63%
“…It has been demonstrated that cyAbrB2 of Synechocystis functions in concert with a global nitrogen regulator, NtcA (17), whose activity is regulated by 2-oxoglutarate (5-9), and the inorganic carbon regulators CmpR and NdhR (21,23). Nitrogen sources (ammonium or nitrate) and/or the CO 2 concentration should affect the 2-oxoglutarate concentration (57) and NtcA activity. However, irrespective of nitrogen sources and CO 2 concentrations, hetP and hepA were similarly induced by calA/cyabrB1 knockdown (Fig.…”
Section: Repression Of Heterocyst Formation In Ammonium Mediummentioning
confidence: 99%
“…We can conclude, therefore, that 2‐OG is the key element in the connection between oxidative stress and N metabolism. Several studies revealed that 2‐OG is a master regulator metabolite in different organisms, including bacteria, plants and humans (Huergo & Dixon, ; Zhang et al ., ). In this sense, our work highlights a new function of this signalling molecule in cyanobacteria.…”
Section: Discussionmentioning
confidence: 97%